La gestion de la sphère travail chez les enseignants du supérieur français. Entre obstacles à surmonter et ressources à capitaliser, quelles stratégies ? - Jacqueline Paquiot-Papet; Florence Cassignol-Bertrand (Éducation et Socialisation)
The aim of this study is to understand the management of the work sphere of university teachers working in the French university system. This sphere is defined by the combination of three activities - research, pedagogy and collective responsibilities. Starting from the idea that the resources of this sphere are limited, as evidenced by a workload perceived as important, the activity model (Curie and Hajjar, 1987, 2000) was chosen in order to approach real activity (Leplat and Hoc, 1983; Yvon and Clot, 2001) of university teachers from the perspective of the resources, constraints and strategies chosen to achieve a possible balance between activities. A qualitative survey was carried out among 10 university teachers. The results show that resources exist, conducive to reconciling activities, while pointing out the existence of constraints conditioning numerous regulatory strategies.